PERFORMANCE EVALUATION OF ADMINISTRATIVE STAFF AT MADRASAH TSANAWIYAH ZIYADATUT TAQWA - Navlia, Rusdiana; Masrurah, Waqiatul; Buna’i; Wahid, Abdul; Munawarah; Mubarokah Sa’bana, Sofia (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2024)
Administrative staff play a crucial role as a supporting pillar for educational quality, yet their performance evaluation is often overlooked. This qualitative study aims to analyze the purpose and inhibiting factors of administrative staff performance evaluation at Madrasah Tsanawiyah Ziyadatut Taqwa, utilizing in-depth interviews, observation, and documentation. The findings reveal that performance evaluation is perceived not as a routine procedure, but as a fundamental strategic instrument to ensure the smooth functioning of the learning ecosystem and uphold educational quality. However, its implementation is hampered by an interlocking web of systemic problems, including a human resource capacity gap (lack of training and technology), structural weaknesses (the absence of a standardized system and poor coordination), and cultural-psychological barriers (high workload and low motivation). This study concludes that a significant gap exists between the ideal vision of evaluation and its implementation reality. A holistic approach is necessary to transform the evaluation process from a formalistic burden into an authentic and functional tool for quality development.